Regulation of biological control agents - Ehlers, Ralf-Udo.; SpringerLink (Online service). (Dordrecht New York Springer, 2011)
This book presents a comprehensive compilation of registration requirements necessary for authorisation of biological control agents (viruses, bacteria, fungi, active substances of natural origin and semiochemicals) in OECD countries. It also reviews data requirements for invertebrate agents (insect, mites and nematodes) and provides proposals for harmonisation of the regulation process and guidelines for completion of application forms. Based on results of the EU REBECA Policy Support Action, which gathered experts from academia, regulation authorities and industry, risks and benefits of the specific agents were reviewed and proposals for a more balanced registration process elaborated, including recommendations for acceleration of the authorisation process and discussions on trade-off effects and policy impacts. All these aspects are covered in detail in this book, which points the way forward for enhanced utilisation of biological control agents.
General Aspects of Regulation -- 1. Regulation of biological control agents and the EU Policy Support Action REBECA -- 2. Regulation according to EU Directive 91/414: data requirements and procedure compared to regulation practice in other OECD countries -- 3. An international comparison of invertebrate biological control agent regulation: what can Europe learn? -- 4. Regulation of plant protection in organic farming -- 5. Policy aspects of regulation -- 6. Cost-benefit, risk and trade-off analysis of regulation -- Risks and Risk Assessment -- 7. Risks of microbial biocontrol agents and regulation: are they in balance? -- 8. Bacterial ecology and human pathogenicity of plant-associated bacteria -- 9. Metabolite toxicology of fungal biocontrol agents -- 10. Risks of biocontrol agents containing compounds of botanical origin or semiochemicals -- 11. Risks of invertebrate biological control agents - Harmonia axyridis as a case study -- Proposals for balanced regulation procedures -- 12. Facilitations in the regulation of plant protection products containing Baculoviruses -- 13. Proposals for bacterial and fungal biocontrol agents -- 14. Proposals for regulation of botanicals -- 15. Proposals for regulation of semiochemicals -- 16. Regulation of invertebrate biological control agents in Europe: recommendations for a harmonised approach -- 17. Proposals on how to accelerate registration of biological control agents -- Index.
Electronic reproduction.
Keywords: Biological pest control agents -- Europe; Biological pest control agents -- Law and legislation -- Europe; Electronic books